ISLAMIC PSYCHOLOGY FROM THE PERSPECTIVES OF AL-KINDI - Fadlul Rahman; Indah Anta Sari; Wahida Raihan Sirait (Edusoshum : Journal of Islamic Education and Social Humanities, 2022)
Islamic psychology was originally a study of humans which should have been a study of human behaviour based on a self-approach to God. After the Islamic world faded, it was replaced by western domination, to which the study of psychology implicitly regressed. This study aims to analyse Islamic psychology from the perspective of Al-kindi, which comes from psychological science. The method used in this study is library research or a review study to obtain theoretical data basis on scientific theory and further select and analyse the literature appropriate to the addressed topics. The investigation showed that, since 1978, Islamic psychology had been an international public discourse. Secondly, according to Al-Kindi, the human soul is divided into three parts: lust, emotion, and rationale. On the other hand, the human soul has three powers: mind, anger, and desire.